Analisis Faktor-faktor yang Mempengaruhi Kualitas Pelayanan Karyawan Perusahaan Daerah Sulawesi Selatan - Yahya, Muhammad; Annas, Suwardi; Sapinah (Jurnal Aplikasi Manajemen, 2014)
This study analyzes the influence of the factors that affect the quality of the service employees Local Company (Perusda) South Sulawesi in terms of the various aspects which include; employee competence, leadership, commitment to work, organizational culture, and organisasial structure, and quality of service of employees. The population in this study were all employees of the company in the area of South Sulawesi Perusda four business units, namely a total of 106 people. The results showed that (1) the value of the variable employee competence and commitment are at very high and variable categories of leadership, organizational culture, organizational structure, and quality of service of employees are in the high category, (2) employee competence and a significant positive effect on the quality of service South Sulawesi Perusda employees, (3) leadership but not significant positive effect on the quality of service of employees (4) work commitments and a significant positive effect on the quality of service of employees (5) organizational culture positive and significant impact on the quality of service of employees (6) organizational structure influence positive and significant impact on the quality of service of employees Pusda in South Sulawesi.